2018
DOI: 10.3892/etm.2018.6131
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of epidermal growth factor and acidic fibroblast growth factor in the treatment of diabetic foot wounds

Abstract: Abstract. The aim of the present study was to investigate the effect of epidermal growth factor (EGF) and acidic fibroblast growth factor (aFGF) on the healing of diabetic foot wounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 40 publications
(30 reference statements)
2
33
0
1
Order By: Relevance
“…FGF. We found four RCTs that evaluated the healing potential of FGF on diabetic ulcers [21][22][23][24] (Tables 5 and 6). Liquid FGF was used, for example, in the form of a spray in different concentrations of 40 U/cm 2 , 100 U/cm 2 , 500 ng/wound, 1 μg/wound, 50 μg/wound, and 500 μg/wound on a daily basis.…”
Section: Morementioning
confidence: 99%
“…FGF. We found four RCTs that evaluated the healing potential of FGF on diabetic ulcers [21][22][23][24] (Tables 5 and 6). Liquid FGF was used, for example, in the form of a spray in different concentrations of 40 U/cm 2 , 100 U/cm 2 , 500 ng/wound, 1 μg/wound, 50 μg/wound, and 500 μg/wound on a daily basis.…”
Section: Morementioning
confidence: 99%
“…(Jung, Yoo and Han, 2016) (Jung, Yoo, & Han, 2016) Medical record 1) Intervention group: hydrophilic polyurethane dressing 2) Saline dressing Total wound healing occurred in 87 patients (polyurethane dressing group) and in 28 patients in the control group within 12 weeks. (Xu et al, 2018) (Xu, Min, Guo, Liao, & Fu, 2018) Experimental: random sampling 1) EFG (Epidermal Grow Factor) Group 2) aFGF (acidic fibroblast growth factor) 3) Combination of EFG and Afgf 4) Normal saline New tissue granulation at grades 2 and 3 needed less treatment time than in the combination group.…”
Section: Improved Healing Of Diabetic Foot Ulcersmentioning
confidence: 99%
“…Among them, acidic fibroblast growth factor (FGF1) is one of the earlier founded members of the fibroblast growth factor family. Studies have shown that FGF1 has a wide range of physiological functions, such as antioxidant damage (Pena et al, 2017), induction of endothelial and smooth muscle cell proliferation and angiogenesis (Zhao et al, 2016), promotion of tissue wound repair (Xu et al, 2018), neurotrophic regeneration (Tsai et al, 2015), etc. Therefore, FGF1 has a great potential in the prevention and treatment of DCM.…”
Section: Introductionmentioning
confidence: 99%